2022
DOI: 10.1007/s12602-022-09913-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Childhood Caries with Probiotic Supplements: A Randomized Controlled Trial with a 12-Month Follow-Up

Abstract: The aim of this study was to evaluate the effect of drops containing probiotic bacteria on the recurrence of dental caries in preschool children. The study employed a randomized, placebo-controlled, double-blinded design with two parallel arms. 38 preschool children were enrolled after comprehensive restorative treatment under general anesthesia or conscious sedation (baseline), and they were followed up after 6 and 12 months. Parents of children in the test group were instructed to give 5 daily drops containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The studies discussed in this collection shed light on the potential advantages of probiotics in enhancing oral health across different contexts. Duraisamy et al (2021) conducted a randomized controlled trial with children, demonstrating that daily probiotic consumption led to a significant reduction in S. mutans levels in saliva [ 30 ]. Sarmento et al (2019) explored the use of probiotic-fortified cheese and its potential to influence the oral microbiota in children [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies discussed in this collection shed light on the potential advantages of probiotics in enhancing oral health across different contexts. Duraisamy et al (2021) conducted a randomized controlled trial with children, demonstrating that daily probiotic consumption led to a significant reduction in S. mutans levels in saliva [ 30 ]. Sarmento et al (2019) explored the use of probiotic-fortified cheese and its potential to influence the oral microbiota in children [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al (2020) found that probiotics improved periodontal health in adults, with reduced bleeding and altered oral bacteria levels [ 38 ]. Finally, Hasslof et al (2022) investigated probiotic drops’ potential to prevent dental caries recurrence in preschoolers, with no significant differences observed between the test and control groups [ 30 ]. These studies collectively underscore the promising role of probiotics in promoting oral health, although their effectiveness may vary, and long-term impacts require further exploration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estes artigos selecionados estão dispostos na Tabela 1. Dos 15 artigos incluídos nessa revisão, apenas 3 não apresentaram resultados detectando a alimentação próbiótica como importante na redução da incidência da cárie dentária ou da diminuição de formação de colônias de Streptococcus mutans ou de Lactobacillus acidophilus(TAIPALE et al, 2013;HASSLÖF et al, 2013;HASSLÖF et al, 2022).Os artigos estudados envolveram um total de 2806 indivíduos. Os veículos para o oferecimento do alimento probiótico foram: o leite em 7 casos(NÄSE et al, 2001; SJOSTROM;TWETMAN, 2009;RODRÍGUEZ et al, 2016; VILLAVICENCIO et al, 2018;PAHUMUNTO et al, 2018;PIWAT et al, 2020;SANDOVAL et al, 2021), gotas (TEHRANI et al, 2016HASSLÖF et al, 2022), pastilhas(ALAMOUDI et al, 2018;STASZCZYK et al, 2022), suco(POHJAVUORI et al, 2010), chupeta (TAIPALE et al, 2013, comprimidos mastigáveis(HEDAYATI HAJIKAND et al, 2015) e dieta com cereais(HASSLÖF et al, 2013).…”
unclassified